(untitled) (Bangladesh Journal of Agricultural Research, 2008)
Primary data from various stakeholders were collected to examine the issues and options in the production of high value crops in coastal region of Pakistan. During 2002, a list of betel leaf and muskmelon growers of Thatta District were developed and out of sampling frame, 160 growers were randomly selected. In the coastal area, growers are engaged in agriculture, fishing, and livestock activities. They keep camel, buffalo, and cattle mainly for milk, which is domestically consumed or sold at village level. The socio-economic conditions of growers living in coastal villages are very poor. Most of the male are unemployed or employed on daily wages. Women are engaged in fish processing industries as unskilled worker and earn a meager income. The analysis of betel leaf and muskmelon was carried out to examine the economic viability of these crops in the coastal region. Analysis shows that these crops have tremendous potential and have no competition in the existing crops in the region. The growers received high net return from betel leaf cultivation and reasonable income from muskmelon cultivation in the coastal region. The major issues for the development of high value crops in the region as identified were high initial cost, poor management operations, low input use, control of insectpests and diseases and lack of knowledge. DOI: http://dx.doi.org/10.3329/bjar.v32i3.537 Bangladesh J. Agril. Res. 32(3) : 359-368, September 2007